Hormones and visual attention to sexual stimuli in older men: an exploratory investigation. (1st January 2021) - Palmer-Hague, Jaime L.; Wong, Samantha T. S.; Wassersug, Richard J.; Kingstone, Alan; Wibowo, Erik
Abstract: Background: Testosterone is associated with sexual desire and performance in men, but little is known about cognitive mechanisms underlying this relationship. Even less is known about the influence of estradiol, despite its production from testosterone, and high receptor density in brain regions related to male sexual behavior. Method: We used eye-tracking to compare men's visual attention to images of fully clothed (i.e. neutral) and minimally clothed (i.e. sexy) models in three groups: androgen-deprived ( n = 6) and not androgen-deprived with prostate cancer ( n = 11), and healthy controls ( n = 7). We also assessed effects of serum testosterone, estradiol, and sex hormone-binding globulin levels. Results: We found no group effect for fixations to sexy compared to neutral images, and no influence of testosterone on either total fixations, or proportion of fixations to sexy images. In contrast, we found that sex hormone binding globulin positively predicted total fixations, and estradiol positively predicted proportion of total fixations on sexy images--regardless of androgen treatment status. Conclusion: Our results suggest that visual attention to sexual stimuli in men may be significantly affected by hormones. This has potential implications for clinical populations that experience sexual side effects, such as prostate cancer patients on androgen deprivation therapy.